Internalization of Sheikh Jumadil Kubro's Da'wah Values for Character Education in History Subjects of the Merdeka Curriculum - Nur Azizah, Ardila; Ayundasari, Lutfiah (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explore and analyze the internalization process of the da'wah (Islamic propagation) values bequeathed by Sheikh Jumadil Kubro and their implementation in shaping students' character through the History subject in the Merdeka Curriculum. Sheikh Jumadil Kubro was a great 14th-century scholar who spread Islam in the Nusantara region. This research employs a qualitative method with a literature study aimed at exploring Sheikh Jumadil Kubro's da'wah values. The research findings reveal that Sheikh Jumadil Kubro possessed three characters relevant to the Pancasila Student Profile: 1) noble character, 2) global diversity, 3) critical reasoning. Thus, the integration of Sheikh Jumadil Kubro's da'wah values into the teaching of History in the Merdeka Curriculum can serve as a relevant model for producing a generation with an Islamic and patriotic character.